2021
DOI: 10.3390/foods10051037
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in Therapy for Food Allergy

Abstract: Food allergy is an increasing problem worldwide, with strict avoidance being classically the only available reliable treatment. The main objective of this review is to cover the latest information about the tools available for the diagnosis and treatment of food allergies. In recent years, many efforts have been made to better understand the humoral and cellular mechanisms involved in food allergy and to improve the strategies for diagnosis and treatment. This review illustrates IgE-mediated food hypersensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 135 publications
0
20
0
1
Order By: Relevance
“…The highest amount of Pru p 3 can be found in the peach peel with a content seven times higher than in the pulp 10,11 . In line with this, peach allergy itself is described as common cause of fresh-fruit allergy 10 .Currently, the main treatment options for peach allergy and food allergies in general are allergen avoidance or symptomatic treatment including anti-histamines as to date no cure or preventive treatment is available [12][13][14] . Due to this lack of treatment options, oral immunotherapy (OIT) might be considered an attractive option to induce immunological tolerance by administration of increasing dosages of allergen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The highest amount of Pru p 3 can be found in the peach peel with a content seven times higher than in the pulp 10,11 . In line with this, peach allergy itself is described as common cause of fresh-fruit allergy 10 .Currently, the main treatment options for peach allergy and food allergies in general are allergen avoidance or symptomatic treatment including anti-histamines as to date no cure or preventive treatment is available [12][13][14] . Due to this lack of treatment options, oral immunotherapy (OIT) might be considered an attractive option to induce immunological tolerance by administration of increasing dosages of allergen.…”
mentioning
confidence: 99%
“…Currently, the main treatment options for peach allergy and food allergies in general are allergen avoidance or symptomatic treatment including anti-histamines as to date no cure or preventive treatment is available [12][13][14] . Due to this lack of treatment options, oral immunotherapy (OIT) might be considered an attractive option to induce immunological tolerance by administration of increasing dosages of allergen.…”
mentioning
confidence: 99%
“…Second, because of the lack of understanding of the pathogenic mechanisms of food allergy, there is a lack of safe and effective treatment options for individuals diagnosed with food allergy. The only safe and effective method for patients with a food allergy diagnosis is to strictly avoid the allergic antigens (11,12). However, there is widespread concern that a strict and limited diet in patients with food allergies can lead to nutritional deficiencies and growth failure in children (13).…”
Section: Introductionmentioning
confidence: 99%
“…Development of FA can be related to some concepts such as the influence of genetic, epigenetic, environmental, and nutritional factors [2], which seem to be involved in its etiology. Genetic studies have shown that there are hundreds of genes in FA that are associated with food-specific IgE, providing strong evidence that genome can determine the complex trait of IgE-mediated FA [3].…”
Section: Introductionmentioning
confidence: 99%